Notes on some type specimens of the Natural History Museum of Pirassununga, São Paulo, Brazil - Azevedo-Santos, Valter M.; Katz, Axel M.; Zawadzki, Cláudio H.; Deprá, Gabriel De Carvalho (Zootaxa, 2023)
Professor Manuel Pereira de Godoy idealized the Natural History Museum of Pirassununga (MHNP, in Portuguese), State of São Paulo, Brazil, in 1938. In 1962, the MHNP was constructed in the backyard of his house. In 1977, the museum also received the type specimens of fishes from the defunct Estação Experimental de Biologia e Piscicultura de Pirassununga (EEBP). Here we provide notes (including photographs) of 11 type specimens (holotypes, paratypes, and syntypes) of the following 10 species belonging to four families and two orders: Leporinus amae, Astyanax (Astyanax) trierythropterus, Hyphessobrycon flammeus guabirubae, Plecostomus fluviatilis, Plecostomus luteus, Plecostomus topavae, Cetopsorhamdia iheringi, Chasmocranus brachynema, Nannorhamdia schubarti, Pimelodella insignis. Our study provides unprecedented photographic records of several type specimens deposited in MHNP. We expect this study will help in species identification and also assist future taxonomic studies of Neotropical freshwater fishes.